Answer:
y = -2
Step-by-step explanation:
y = -5x + 13
x = 3
y = -5(3) + 13
y = -15 + 13
y = -2
9514 1404 393
Answer:
multiply by 3 and divide by 2 to get 6x -y = 12.
Step-by-step explanation:
A standard form equation has mutually prime integers for coefficients, and the leading one is positive. We can get that here by multiplying by 3 (to eliminate the denominator) and dividing by 2 (to remove that common factor). The result is ...
4(3/2)x -(2/3)(3/2)y = 8(3/2)
6x -y = 12
72 degrees
*********************************************************************
Whats the problem ur having in high school youngin